Prevalence of non-functional overreaching and the overtraining syndrome in Swiss elite athletes - Birrer, D.; Lienhard, D.; Williams, G. A.; Röthlin, P.; Morgan, G. (Schweizerische Zeitschrift für Sportmedizin und Sporttraumatologie, 2013)
Objectives: Fatigue and unaccountable underperformance are common for athletes, but there is a lack of empirical data regarding the prevalence of non-functional overreaching (NFOR) and the overtraining syndrome (OTS). Using the overtraining definition of the European College of Sport Science (ECSS), the present study aimed to explore the prevalence, symptoms and associated factors of NFOR/OTS across Swiss elite athletes in various sports. Method: 139 Swiss elite athletes (63 males and 76 females, Mage = 23.6, SDage = 5.6 y) from 26 different sports completed a1 7-item online survey about underperformance and symptoms of NFOR/OTS. 95% of the sample represented Switzerland in their sport. Athletes were classified as NFOR/ OTS by according to the overtraining definition of the ECSS. Data were analysed using Mann-Whitney U nonparametric tests and ANOVAs. Results: 9% of the athletes were classified as OTS and 21% as NFOR at least once in their career. The prevalence was significantly higher in medium-physical demand sports than in low-physical demand sports (p = .02). There were no significant differences in the NFOR/OTS prevalence between individual and team sports and female and male athletes. Competition level and training load had also no significant influence on the NFOR/OTS prevalence, although low-physical demand sports trained significantly less than medium- and high-physical demand sports. Injury/illness, loss of weight and sleep disturbance rates were significantly higher in the NFOR/OTS group. More than 70% of the NFOR/OTS athletes reported loss of motivation and emotional disturbances. Conclusions: The NFOR/OTS career prevalence rate of Swiss elite athletes can be estimated at approximately 30%. NFOR/OTS is accompanied by biopsychosocial signs of maladjustment, e.g., emotional disturbances, loss of motivation, sleep disturbances, injury/illness and weight loss, but training load is not a predictor of NFOR/OTS.